Genetic diversity and diversification patterns of puma (Puma concolor) populations in the southern end of the species distribution - Mac Allister, Matias E.; Figueroa, Carlos E.; Mazzei, Regina; Tintorelli, Ramiro G.; Acosta, Diana B.; Gallo, Orlando; Castillo, Diego; Pinardi, Emiliano; Zelada Perrone, Virginia D.; Rodríguez, Alejandro; Zanón Martínez, Juan I.; Merino, Mariano L.; et al. (Frontiers in Ecology and Evolution, 2024)
The puma (Puma concolor Linnaeus, 1771) is the top predator with the widest distribution in America. Since the establishment of European settlers on the American continent, puma populations have experienced significant contractions and reductions in their original distribution. In Argentina, the management of the conflict between humans and pumas (direct persecution and habitat modification) focused on reduction or elimination methods, leading to a drastic contraction, even total eradication, of puma populations as seen in Patagonia and the eastern part of the country. Despite the lack of knowledge about puma population demographic trends, there are taxonomic issues that remain controversial and need to be resolved to implement appropriate management and conservation measures. Therefore, the aim of this study was to genetically characterize puma populations in the central-southern region of Argentina using two mitochondrial markers, evaluate their demographic history, compare our results at a macro-regional level, and discuss our findings in a conservation and management context. A total of 203 individuals were used, and a fragment of the control region and another of ND5 were sequenced. The genetic variability obtained was moderate. Substitution rates for each locus and the tMRCA were calculated from calibrated trees. In a concatenated tree, two main phylogenetic clades were identified (posterior probability = 1), although a reciprocal monophyly was not observed, with a divergence time of 228 thousand years and a 95% CI [117–363 thousand years]. When evaluating population structuring, three genetic clusters were found, one characteristic of the Patagonian region and the others in the central part of the country. Calculating the ФST values for pairs resulted in significant structuring between Patagonia and the rest of the populations, suggesting the arid diagonal as a possible barrier to gene flow. When evaluating the demographic history, neutrality tests would support a recent expansion in Patagonia. These findings are crucial in defining two distinct Management Units (MUs) in the southern part of puma distribution and providing valuable information for management and conservation measures for the species.